Respuesta :
Answer:
[tex]sin(30\°)*sin(60\°)=cos(60\°)*cos(30\°)[/tex]
Step-by-step explanation:
we know that
[tex]sin(\alpha)=cos(\beta)[/tex]
when
[tex]\alpha+\beta=90\°[/tex] -------> complementary angles
so
[tex]sin(30\°)=cos(60\°)[/tex]
[tex]sin(60\°)=cos(30\°)[/tex]
Because
[tex]30\°+60\°=90\°[/tex] -------> complementary angles
In this problem the product of
[tex]sin(30\°)*sin(60\°)[/tex]
is equal to
[tex]cos(60\°)*cos(30\°)[/tex]
therefore
[tex]sin(30\°)*sin(60\°)=cos(60\°)*cos(30\°)[/tex]